496 A fatal case of MitraClip thrombosis. (17th January 2020) - Andrikopoulou, E; Mitchell, R N M; Kim, A Y K; Shook, D C S; Kaneko, T K; Shah, P B S; Sun, Y P S
Abstract: Case: An 80 year old man presented with persistent dyspnea two months following placement of three MitraClip devices for severe degenerative mitral regurgitation (MR). On exam, he had an apical holosystolic murmur. A transesophageal echocardiogram revealed displacement of one of the MitraClip devices (Figure 1A, red arrow showing the displaced MitraClip) and moderate-severe MR (Figure 1B). He underwent implantation of a fourth MitraClip with reduction of his MR to mild-moderate (Figure 1C, 1D; yellow arrow showing the new MitraClip). Shortly after, he experienced severe melena and hematochezia and became lethargic and hypotensive. He was transferred to the Cardiac Intensive Care Unit, was intubated and aggressively supported. Extensive work-up revealed diffuse gastric body ischemia and ulceration. A transthoracic echocardiogram showed his most recent MitraClip being well seated with mild-moderate MR. He developed refractory multi-organ failure and expired eight days following the procedure. Autopsy revealed thrombi attached to the initially placed MitraClip's (Figure 1E, 1F) and thromboemboli to the small bowel, spleen and brain. Discussion: MitraClip is the predominant non-surgical alternative for percutaneous mitral valve repair in inoperable patients with symptomatic MR, either primary or secondary. Despite its growing use, there remains a paucity of data on its safety and the potential life-threatening complications, especially when more than one device are placed. Current recommendations include dual antiplatelet therapy with aspirin and clopidogrel. In patients already on anticoagulation, continuation of it is recommended. Very few cases of MitraClip thrombosis have been reported so far. Acute development of spontaneous echo contrast (SEC) and early thrombus was described in a patient with severe, primary MR receiving 2 MitraClip"s. Both SEC and the early thrombus resolved once the second device was removed. In another case, intraprocedural thrombus formation was described on the right side of the interatrial septum close to the MitraClip guide catheter. The underlying pathophysiologic mechanism and the predisposing factors to acute and subacute thrombosis associated with MitraClip are unclear. One plausible explanation could be the acute dramatic hemodynamic alterations related to the reduction in MR and new mild mitral stenosis. In addition, the MitraClip itself may act as a prothrombotic nidus. Potential risk factors include: advanced age and multiple comorbidities predisposing to proinflammation and prothrombosis. The use of MitraClip is only expected to increase in the future. Large scale clinical trials are needed to further define the safety of the device and delineate the optimal antiplatelet and/or antithrombotic regimen.